Modulation of LPS stimulated NF-kappaB mediated Nitric Oxide production by PKCε and JAK2 in RAW macrophages - Ahmed Bushra Y; Adcock Ian M; Jones Edward; Punchard Neville A (BMC, 2007)
Abstract Background Nuclear factor kappa B (NF-κB) has been shown to play an important role in regulating the expression of many genes involved in cell survival, immunity and in the inflammatory processes. NF-κB activation upregulates inducible nitric oxide synthase leading to enhanced nitric oxide production during an inflammatory response. NF-κB activation is regulated by distinct kinase pathways independent of inhibitor of κB kinase (IKK). Here, we examine the role of protein kinase C isoforms and janus activated kinase 2 (JAK2) activation in NF-κB activation and LPS-stimulated NO production. Methods Murine RAW 264.7 macrophages were treated with lipopolysaccharide (LPS), Phorbol 12-myristate 13-acetate (PMA) and a combination of LPS and PMA in the presence or absence of various inhibitors of PKC isoforms and JAK2. Nuclear translocation of the NF-κB p65 subunit, was assessed by Western blot analysis whilst NO levels were assessed by Greiss assay. Results LPS-stimulated NO production was attenuated by PMA whilst PMA alone did not affect NO release. These effects were associated with changes in p65 nuclear translocation. The PKCα, β, γ, δ and ζ inhibitor Gö 6983 (Go) had no effect on LPS-induced NO release. In contrast, Bisindolymalemide I (Bis), a PKC α, βI, βII, γ, δ and ε isoform inhibitors completely inhibited LPS-stimulated NO production without affecting p65 nuclear translocation. Furthermore, a partial inhibitory effect on LPS-induced NO release was seen with the JAK2 inhibitor AG-490 and the p38 MAPK inhibitor SB 203850. Conclusion The results further define the role of NF-κB in LPS stimulated NO production in RAW macrophages. The data support a function for PKCε, JAK2 and p38 MAPK in NF-κB activation following p65 nuclear import.